Effect of pH on Penetration of Naphthaleneacetic Acid and Naphthaleneacetamide Through Isolated Pear Leaf Cuticle - Norris, Robert F. (1972)
Penetration of naphthaleneacetic acid through enzymatically isolated upper pear (Pyrus communis L. cv. Bartlett) leaf cuticle increased as the donor pH was decreased. Naphthaleneacetamide penetration was not influenced by donor pH. The effect of pH on naphthaleneacetic acid penetration was reversible. Higher receiver (simulated leaf interior) pH favored penetration of naphthaleneacetic acid. Changes in the degree of dissociation, and hence polarity, as controlled by hydrogen ion concentration was the prime factor in the response of naphthaleneacetic acid to pH. At pH values lower than the pK (4.2 for naphthaleneacetic acid), the molecule was primarily undissociated, lipophilic, and penetrated into the cuticle; whereas, at pH values above the pK naphthaleneacetic acid was ionized, hydrophilic, and penetrated the cuticle with difficulty or not at all. Data presented are consistent with the hypothesis that naphthaleneacetic acid and naphthaleneacetamide penetration through the cuticle takes place by diffusion.